Identification of microplastic-associated microbial communities from various stages of wastewater treatment and recipient surface waters using MALDI-TOF mass spectrometry - Mothoa, Lerato Emelda; Prikler, Bence; Szabó, István; Micsinai, Adrienn; Kaszab, Edit (Journal of Central European Green Innovation, 2025)
Recent studies have identified microplastics (MPs) in wastewater as surfaces that facilitate microbial colonization and act as vectors for the dissemination of antibiotic resistance genes (ARGs) and antibiotic-resistant bacteria (ARBs). Their presence throughout the wastewater treatment process highlights the importance of investigating the microbial communities associated with MPs in wastewater treatment plants (WWTPs) and their potential implications for environmental and human health. This study investigates microbial colonization on MPs in wastewater by sampling six types of MPs deployed at various phases of wastewater treatment in three different WWTPs across Hungary, between June 2024 and March 2025. MPs were incubated in plastic colonizers submerged in treated and untreated wastewater. Post-retrieval, MPs were processed using selective media to ARBs, using Chromatic agar plates and selective medium for Pseudomonas aeruginosa. Strains were identified by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) at the genus level. Based on our results, Stenotrophomonas, Aeromonas genera, and members of the Enterobacteriaceae family were the dominant antibiotic-resistant bacterial taxa associated with MPs.
Keywords: microplastic; wastewater; Aeromonas; Stenotrophomonas; MALDI-TOF MS